2015
DOI: 10.1038/srep10673
|View full text |Cite
|
Sign up to set email alerts
|

A new mib allele with a chromosomal deletion covering foxc1a exhibits anterior somite specification defect

Abstract: mibnn2002, found from an allele screen, showed early segmentation defect and severe cell death phenotypes, which are different from previously known mib mutants. Despite distinct morphological phenotypes, the typical mib molecular phenotypes: her4 down-regulation, neurogenic phenotype and cold sensitive dlc expression pattern, still remained. The linkage analysis also indicated that mibnn2002 is a new mib allele. Failure of specification in anterior 7-10 somites is likely due to lack of foxc1a expression in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…S4B arrowheads), the formation of somites 1-4 was abnormal in foxc1a mutants ( Fig. S4A, C, E, F red arrowheads, G) consistent with previous reports (Hsu et al, 2015;Li et al, 2015). In addition, foxc1a mutants displayed a significant increase in somitic angle of posterior somites ( Fig S4E, F, H), which likely accounts for straightened ISVs in these mutants.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…S4B arrowheads), the formation of somites 1-4 was abnormal in foxc1a mutants ( Fig. S4A, C, E, F red arrowheads, G) consistent with previous reports (Hsu et al, 2015;Li et al, 2015). In addition, foxc1a mutants displayed a significant increase in somitic angle of posterior somites ( Fig S4E, F, H), which likely accounts for straightened ISVs in these mutants.…”
Section: Resultssupporting
confidence: 90%
“…In addition, knockdown of foxc1a/b in zebrafish has been reported to reduce Etv2 promoter activity, suggesting these genes also function upstream of Etv2 (Veldman and Lin, 2012). Several recent studies using foxc1a mutants have indicated a requirement for foxc1a during neural circuit development (Banerjee et al, 2015) in addition to anterior somite formation (Hsu et al, 2015;Li et al, 2015) which is consistent with previous knockdown studies (Topczewska et al, 2001b).…”
Section: While Angiogenesis Is Tightly Regulated By Interactions Betwsupporting
confidence: 88%
See 1 more Smart Citation
“…6A-D). A similar analysis revealed no obvious difference for elavl3, a nervous system marker for the differentiation of the ectoderm (33), between adtrp1 morphants and control embryos that were injected with Std-MO (Supplemental Fig. 6E, F).…”
Section: Effect Of Adtrp1 On the Specification Of Vascular Endotheliamentioning
confidence: 62%
“…Accumulating evidence in recent years suggests that Foxc1 has an important, dose dependent role in somite formation and axial skeletal development [20,[22][23][24]. Mice with null Foxc1 mutations have defects in axial skeletal development, such as incomplete formation of the neural arches, misshapen ribs, and fused vertebrae, along with cardiovascular, ocular and other anomalies [20].…”
Section: Discussionmentioning
confidence: 99%